Estimating the cost of vaccination in southeastern Iran. Issue 10 (2nd October 2020) - Goudarzi, Reza; Tasavon Gholamhoseini, Mohammad; Amini, Saeed; Nakhaei, Mahsa; Dehnavieh, Reza
ABSTRACT: Background : Specification of vaccination cost of children would help policymakers in determining the nation-wide budget needed for the maintenance of the vaccination program. The budget came these days under scrutiny due to the imposed sanctions tightening the public funds. This study aims at estimating the cost of vaccination in southeastern Iran for obtaining more accurate budget projections. Methods : Fifty-two healthcare centers from 10 cities in south-east Iran participated in using a quota sampling method for their selection. A bottom-up method determined the human resource use, the consumption, and the overhead costs to estimate the cost of vaccination. Data collection used a standard tool that was adjusted to local conditions. Sensitivity analyses were performed. Results : The overall vaccination cost for the region was estimated at around 5, 984, 000 USD for the year 2015. Salaries took the largest part of the cost estimate (64%), while vaccine cost and its equipment were much lower (22%). The average cost per vaccine dose administrated was 40.94 USD. Sensitivity analysis of the population and inflation rate indicates that the vaccination cost may fluctuate between 37% and 53% over 6 years (2021) from the data of 2015. Conclusion : Maintaining vaccination has a substantial cost. The results of the study will support the budget planning and decision making and will define more precisely the resource allocation needed for maintaining the vaccination at a high level across the country. It may also help to facilitate the assessment of cost-benefit and cost-effectiveness analysis when new vaccines should be introduced.